Nursing care challenges of child violence victims: A qualitative study - Nazila Vosoghi; Masoud Fallahi-Khoshknab; Mohammadali Hosseini; Fazlollah Ahmadi (Wolters Kluwer Medknow Publications, 2021)
Background: Violence against children is a serious global phenomenon. The severity of the injuries caused due to violence toward a child is sometimes so great that it sends them to the hospital. Nurses have the first contact with Child Violence Victims (CVVs). These nurses experience different challenges. This study was aimed at exploring nurses' experiences of challenges in care provision to CVVs. Materials and Methods: This conventional content analysis and qualitative study was conducted in 2018-2019. Using a purposive sampling method, 17 nurses with experience in care delivery to CVVs were recruited from among those working in Children's Medical Center, Tehran, Iran, and Bu-Ali Subspecialty Hospital, Ardabil, Iran. In-depth semi-structured interviews were conducted to collect the required data. Data were analyzed through the conventional content analysis method. Results: During data analysis, the 3 main categories of role conflict, lack of continuity of care, and emotional resentment and 9 subcategories were identified. Nurses experience challenges in care provision to CVVs. They do not have enough knowledge about CVVs, are unable to maintain the continuity of care, and experience role conflicts and emotional resentment. Conclusions: Nurses experience some difficulties and challenges in the process of care delivery to CVVs. They tried to overcome emotional resentment, different conflicts, and concerns about the lack of continuity of care without adequate support and resources. Thus, planning to support nurses in this regard seems essential.